2020
DOI: 10.1016/j.omtn.2020.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Immune Cell Infiltration Landscape in Head and Neck Squamous Cell Carcinoma to Aid Immunotherapy

Abstract: The tumor microenvironment (TME) chiefly consists of tumor cells and tumor-infiltrating immune cells admixed with the stromal component. A recent clinical trial has shown that the tumor immune cell infiltration (ICI) is correlated with the sensitivity to immunotherapy and the head and neck squamous cell carcinoma (HNSC) prognosis. However, to date, the immune infiltrative landscape of HNSC has not yet been elucidated. Herein, we proposed two computational algorithms to unravel the ICI landscape of 1,029 HNSC p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(172 citation statements)
references
References 52 publications
12
159
1
Order By: Relevance
“…We compared the predictive ability of the signature genes in our study and other models in terms of the immunotherapy benefit. We selected signature genes identified by the INF model and the HNSC model ( 15 , 24 ). The Kaplan-Meier curves and the ROC curves of the ICI score of the other two models are shown in Fig S4A-F. For the other two models, there were no statistically significant differences in the overall survival between those with high and low ICI scores, and the prognosis differed among the cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared the predictive ability of the signature genes in our study and other models in terms of the immunotherapy benefit. We selected signature genes identified by the INF model and the HNSC model ( 15 , 24 ). The Kaplan-Meier curves and the ROC curves of the ICI score of the other two models are shown in Fig S4A-F. For the other two models, there were no statistically significant differences in the overall survival between those with high and low ICI scores, and the prognosis differed among the cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the predictive ability of the signature genes in our study and other models in terms of the immunotherapy benefit. We selected signature genes identified by the INF model and the HNSC model (15,24). The Kaplan-Meier curves and the ROC curves of the ICI score of the other two models are shown in Fig S4A-F.…”
Section: Predictive Value Of the Ici Scores For Clinical Characteristics And Immunotherapy Benefitmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, CD8 + T cell status correlated with the composition of myeloid populations. Recently, accumulating evidence suggested that immune cell infiltration was closely tied with levels of immune activity in the TIME of HNSCC ( 15 , 73 ), and immune infiltration could be evaluated using various models constructed by different methods, such as cancer-associated AS events (CASEs) and m 6 A methylation regulators ( 74 , 75 ). Some of the myeloid genes in our model have been shown to regulate multiple immune cells by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we obtained the signature genes A and signature genes B. Finally, the principal components analysis (PCA) was used to calculate the first principal components of signature genes A and B in each sample ( Zhang X. et al, 2020 ). The ubiquitin scores of each sample were extracted as:…”
Section: Methodsmentioning
confidence: 99%